Is transcutaneous electrical nerve stimulation an effective analgesia during colonoscopy?. Issue 909 (1st July 2001) - Robinson, R; Darlow, S; Wright, S J; Watters, C; Carr, I; Gadsby, G; Mayberry, J
Abstract : OBJECTIVES: To evaluate the efficacy of transcutaneous electrical nerve stimulation (TENS) as analgesia during colonoscopy. DESIGN: In a randomised controlled trial, patients undergoing diagnostic colonoscopy were assigned to one of three groups: standard medication only (midazolam); active TENS plus standard medication; or non-functioning TENS and standard medication. Efficacy of TENS was determined using numerical rating scores for pain and the post-procedural evaluation questionnaire. SETTING: Patients undergoing diagnostic colonoscopy in a teaching hospital. MAIN OUTCOME: There was no statistically significant differences between the three groups. However in the active TENS group there was a greater variation in "physical discomfort" and "psychological distress", suggesting TENS may be effective in subgroup of patients.